2008
DOI: 10.1002/cncr.23416
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer adjuvant chemotherapy dosing in obese patients

Abstract: BACKGROUND Substantial variation in adjuvant breast cancer chemotherapy dosing in obese women suggests that there is uncertainty about optimal practices. The purpose of this study was to investigate variations in dose determinations in clinical trial protocols and publications over the last 3 decades as potential sources of this uncertainty. METHODS The National Cancer Institute database was used to identify protocols of breast cancer adjuvant chemotherapy conducted by cooperative groups between 1970–2000, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, multiple retrospective analyses observed that obese women treated for breast cancer using ABW did not have increased toxicity compared with normal women. 17,19,20 Altering the number of CMs in our survey did not affect EDA.…”
Section: Percentage Of Patientsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, multiple retrospective analyses observed that obese women treated for breast cancer using ABW did not have increased toxicity compared with normal women. 17,19,20 Altering the number of CMs in our survey did not affect EDA.…”
Section: Percentage Of Patientsmentioning
confidence: 76%
“…17,18 An analysis of breast cancer adjuvant chemotherapy protocols from 1970 to 2000 also demonstrated this change over time. 19 Before 1984, 95% of these trials permitted use of EDA for obesity; since 1984, that amount has decreased to 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Greenman et al recommended that given the increase in prevalence of obesity and extreme obesity, guideline-development groups should provide information on standard of care practices for dosing obese breast cancer patients who are receiving adjuvant chemotherapy [31]. This study provides preliminary evidence that in a select clinical setting, physician recommendations regarding use of adjuvant chemotherapy for breast cancer are not influenced by patient weight.…”
Section: Discussionmentioning
confidence: 90%
“…From the treatment perspective, obese women may be underdosed for chemotherapy due to toxicity-related concerns, resulting in reduced therapeutic response and worse outcomes [47-49]. However, when we stratified the obese women in our cohort by receipt of chemotherapy, no prognostic risk differences were observed by chemotherapy status.…”
Section: Discussionmentioning
confidence: 99%